Pendampingan Pastoral Terhadap Keluarga Yang Tidak Memiliki Keturunan Untuk Mencegah Perceraian - Mindo Rina Tampubolon (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The family is a social unit in the order of society. The family is also an institutional subsystem or smallest unit in a larger social system, such as society, nation and state. The family consists of people who are bound by marriage, blood relationship or adoption, family members who live under one roof (house), there is interaction and communication according to their respective roles, as well as passing down habits or culture in general and practicing them independently. The family is a biosocial institution formed by at least two adults, a man and a woman who are not related by blood or have no children. Every family certainly has a goal and one of them is to have children. However, not all married couples are successful in terms of having harmony. For some families, this is not a problem because they can react to it positively. However, for some families, not having children is something that triggers problems in their household and this is also experienced by several married couples in the church. For this reason, it is necessary to provide pastoral assistance to families who do not have children to prevent divorce. The author uses a qualitative approach. The qualitative approach emphasizes the search for meaning, understanding, concepts and descriptions of a phenomenon; prioritizes quality, and is presented narratively. Research data was collected through interviews. The author conducted open interviews so as not to limit informants from conveying their understanding about the absence of children in their family. And the informants were four families from four churches in Region 1 GPP Medan - Langkat.